The Influence of Celebrity Endorsement and Brand Image on Purchase Intention with Brand Awareness as An Intervening Variable: Case Study of Scarlett Whitening Products in Soloraya - Putra Yuwana, Wahyu Noer Hidayat; Lestari, Wuryaningsih Dwi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research reveals the significant impact of brand awareness and celebrity endorsement on purchase intention, particularly within the context of Scarlett products. The analysis confirms that the level of brand awareness correlates significantly with consumers' inclination to purchase products. These findings highlight the necessity of building brand awareness as an effective marketing strategy, using engaging advertising campaigns, presence across various media platforms, and involvement in social activities or sponsorship of popular events. Furthermore, the study confirms that the brand image of Scarlett products holds a crucial influence on brand awareness. Positive brand image elements such as strong slogans, product quality, and memorable packaging contribute to enhancing brand awareness among consumers. On the other hand, celebrity endorsements also prove to have a substantial impact on purchase intention. The presence of celebrities in advertisements captures consumers' attention, influences their perceptions of the brand and product, and increases their interest in purchasing. Selecting the right celebrities becomes an effective strategy for influencing consumer purchasing behavior. The results of this research provide profound insights into the importance of brand awareness, brand image, and celebrity endorsement in influencing consumer behavior, while also highlighting potential marketing strategies that companies can employ to enhance purchase intention.